Management of patients with vulvovaginal atrophy and cytological abnormalities - Niso M. Nazarova; Vera N. Prilepskaya; Anna N. Mgeryan; Elmira R. Dovletkhanova; Patimat R. Abakarova; Elena A. Mezhevitinova (IP Berlin A.V., 2023)
The data on managing patients with vulvovaginal atrophy and abnormal cytological results are provided for obstetrician-gynecologists.